Were Temple Offerings Buried at Qumran? - Mizzi, Dennis (Biblical archaeology review, 2023)
The article discusses the peculiar burial of sealed pottery jars, once filled with date honey, in the Qumran cemetery, shedding light on the possible religious significance of this practice among the site's inhabitants. Topics include the unique custom of burying these jars, potential reasons behind their burial, and the implications for understanding the religious beliefs and social dynamics of the Qumran community.